INCREASING THE WEAR RESISTANCE OF THE FRICTION STEAM PISTON-CYLINDER OF THE HIGH PRESSURE CAR WASH PUMP - SVIDERSRKYI, VLADYSLAV; SIRENK, GENNADIY (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The analysis of the operation of the high-pressure car wash and the axial piston pump included in its composition was performed. The pump body is usually made of any metal or alloy (for example, aluminum or stainless steel), and the pistons are made of specially hardened steel. Since such units have a short service life, the question of their motor resource is quite relevant. In professional car washes, pistons made of metal ceramics and heat-resistant composite polymer materials are promising.The choice of material for replacing the base material of the axial pump piston is justified. According to the complex of physical and mechanical indicators, aromatic polyamide Fenilon-C2 and aromatic polyamide PM-69 prevail over most industrial plastics. Parts made of aromatic polyamide and polyimide withstand loads close to those permissible for non-ferrous metals and alloys, and their wear resistance is higher than that of metals. This made it possible to recommend them for use as high-pressure car wash pump pistons. Increasing the wear resistance of composite polymer materials based on aromatic polyamide Fenylon C-2 and aromatic polyimide PM-69 was carried out as a result of their modification with graphite and non-woven powders. Laboratory studies of the wear resistance of antifriction materials of pistons of axial-piston hydraulic machines showed the feasibility of using materials based on aromatic polyamide PM-69 and aromatic polyamide Fenylon C-2 as pistons or cylinder liners. It was found that the material based on aromatic polyimide PM-69 (60 wt.%) and fluoroplast-4 (40 wt.%). Aromatic polyimide PM-69 has much less water absorption - 0.2-0.3 wt. % and this is its significant advantage over the aromatic polyamide Fenilon C-2. In addition, the aromatic polyamide PM-69 has significantly less water absorption, and this is its significant advantage over the aromatic polyamide Fenilon C-2.
Keywords: high-pressure car wash; wear resistance; axial piston pump; anti-friction materials based on aromatic polyamide Fenylon C-2 and aromatic polyamide PM-69; cylinder liner